FORMULATION OF HAND AND BODY LOTION BASED ON VIRGIN COCONUT OIL (VCO) AND COCONUT OIL WITH BUTTERFLY PEA FLOWER (Clitoria ternatea L.) EXTRACT AS ANTIOXIDANT - Syarifah Al Haura; E Elwina; Zuhra Amalia (Jurnal Sains dan Teknologi Reaksi, 2026)
Hand and body lotion is a cosmetic preparation used for skin care. Butterfly pea extract (Clitoria ternatea L.) was selected due to its anthocyanin, flavonoid, and phenolic content, which act as natural antioxidants. This study aims to formulate hand and body lotion based on Virgin Coconut Oil (VCO), coconut oil, and butterfly pea extract, and to evaluate its physical, chemical, and antioxidant properties. The extract was obtained through maceration using 70% ethanol with a yield of 37.28%. Lotion formulations were prepared with various ratios of VCO:Coconut Oil (1:0, 3:1, 1:1, 1:3, 0:1) and butterfly pea extract additions of 1–5 mL. The results showed that all formulations met SNI 16-3499-1996 standards with pH ranging from 5.0 to 6.6, viscosity between 43,000–47,000 cP, and specific gravity between 0.95–1.03 g/mL. Organoleptic tests indicated that the VCO:Coconut Oil ratio of 1:0 with 1– 3 mL extract was the most preferred by panelists. Antioxidant activity analysis yielded an IC50 value of 1.54 ppm, indicating very strong activity. The study concludes that the combination of Virgin Coconut Oil, coconut oil, and butterfly pea extract significantly affects the physical and antioxidant characteristics of the produced hand and body lotion.Keywords: Antioxidant, Butterfly Pea Extract, Hand and Body Lotion, Coconut Oil, Virgin Coconut Oil